Emotion work and the children of the Chilean exile, 50 years on. - Díaz Cerda, Verónica (Journal of Ethnic & Migration Studies, 2025)
Despite recent attempts to broaden the scope of migration research beyond its adult-centric focus, the experiences of forced displaced children remain underexplored. This article aims to address that gap by examining retrospectively how the children of the Chilean exile understood the rupture enacted by displacement during Pinochet dictatorship. To that end, it uses what Arlie Hochschild has termed 'emotion work' as a framework for analysing the agency exercised by the children who arrived in the UK, escaping from the dictatorship, as well as those born in Britain to parents who had fled it. Drawing upon fieldwork, this article argues that the active efforts by these children to suppress or evoke emotions within their families, aimed at creating a semblance of normality that helped to sustain or recover the everyday of their parents' lives, suspended in time. While many studies have emphasised the present as the primary site for exploring child's migrant agency, this article reconceptualises it in relation to the past, by recovering the child's gaze embedded within the affective narratives articulated by participants. In this way, it also seeks to rectify the absence of childhood voices in the academic literature and public debates on memory and exile in Chile.